1981
DOI: 10.1017/s0033583500002079
|View full text |Cite
|
Sign up to set email alerts
|

Functional reassembly of membrane proteins in planar lipid bilayers

Abstract: Recent progress in membrane biology has brought us to a stage where it is possible to associate complex biological processes to identifiable membrane proteins. Technical advances in the biochemical characterization and purification of membrane proteins have contributed a wealth of structural information. The reconstitution approach has proved to be valuable in our efforts to understand the molecular mechanisms of membrane transport and energy transduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(31 citation statements)
references
References 213 publications
1
30
0
Order By: Relevance
“…As to the light-induced rise of Ca 2+ permeability of a rhodopsin-containing membrane, it is apparently very rapid. In our experiments on photoreceptor discs incorporated into a collodion film [2], we not only confirmed observations on the light-dependent increase in disc membrane permeability [24,[42][43][44][45][46][47][48][49][50] but also revealed that such an effect requires < 50 ms. (A faster measurement is impossible because of a conductivity increase due to operation of rhodopsin as a photogenerator of much lower internal resistance than that of the disc membrane. )…”
Section: The 'Dualistic' Schemesupporting
confidence: 88%
See 1 more Smart Citation
“…As to the light-induced rise of Ca 2+ permeability of a rhodopsin-containing membrane, it is apparently very rapid. In our experiments on photoreceptor discs incorporated into a collodion film [2], we not only confirmed observations on the light-dependent increase in disc membrane permeability [24,[42][43][44][45][46][47][48][49][50] but also revealed that such an effect requires < 50 ms. (A faster measurement is impossible because of a conductivity increase due to operation of rhodopsin as a photogenerator of much lower internal resistance than that of the disc membrane. )…”
Section: The 'Dualistic' Schemesupporting
confidence: 88%
“…One cannot rule out that the Ca 2+ pathway does not reach the Na + channel, and the role of Ca 2+ in vision is confined to their effect on the cGMP system (e.g., [7,43]). In this case, however, more than one step of amplification seems to be involved in the Ca 2+ pathway, so that a stimulus and the response prove to be separated by a lagphase [41].…”
Section: Interrelations Of Fast and Slow Pathwaysmentioning
confidence: 99%
“…Thus, in the monograph published in 1975, the catalytic activity of enzymes in aqueous surfactant solutions is discussed only in a small chapter [104], and in the monograph published seven years later [64] this topic was totally omitted. Such a strange situation can be easily explained by the fact that many of anzymologists consider surfactants to be merely denaturing agents [3, 93, 112, 1131. Actually, the interaction between surfactants and proteins in aqueous solutions can be rather specific [110, 116- [57]). …”
Section: Micellar (Pseudohomogeneous) Models Of Biological Membranesmentioning
confidence: 99%
“…BLMs may also be formed at the end of conventional patch-clamp pipettes [201][202][203] with tip diameters in the range 0.5-5 mm either with or without fire polishing [197,[204][205][206]. With this so-called tip-dip technique, the tip of the pipette is immersed in the desired experimental solution in a compartment of a multi-well disposable tray, and a phospholipid monolayer is formed at the air-water interface.…”
Section: Planar Lipid Membranesmentioning
confidence: 99%